Expression of the schizophrenia associated gene FEZ1 in the early developing fetal human forebrain - Alhesain, Maznah; Ronan, Hannah; LeBeau, Fiona E. N.; Clowry, Gavin J. (Frontiers in Neuroscience, 2023)
The protein fasciculation and elongation zeta-1 (FEZ1) is involved in axon outgrowth but potentially interacts with various proteins with roles ranging from intracellular transport to transcription regulation. Gene association and other studies have identified FEZ1 as being directly, or indirectly, implicated in schizophrenia susceptibility. To explore potential roles in normal early human forebrain neurodevelopment, we mapped FEZ1 expression by region and cell type. All tissues were provided with maternal consent and ethical approval by the Human Developmental Biology Resource. RNAseq data were obtained from previously published sources. Thin paraffin sections from 8-21 postconceptional weeks (PCW) samples were used for RNAScope in situ hybridization and immunohistochemistry against FEZ1 mRNA and protein, and other marker proteins. Tissue RNAseq revealed that FEZ1 is highly expressed in the human cerebral cortex between 7.5-17 PCW and single cell RNAseq at 17-18 PCW confirmed its expression in all neuroectoderm derived cells. The highest levels were found in more mature glutamatergic neurons, the lowest in GABAergic neurons and dividing progenitors. In the thalamus, single cell RNAseq similarly confirmed expression in multiple cell types. In cerebral cortex sections at 8-10 PCW, strong expression of mRNA and protein appeared confined to post-mitotic neurons, with low expression seen in progenitor zones. Protein expression was observed in some axon tracts by 16-19 PCW. However, in sub-cortical regions, FEZ1 was highly expressed in progenitor zones at early developmental stages, showing lower expression in postmitotic cells. FEZ1 has different expression patterns and potentially diverse functions in discrete forebrain regions during prenatal human development.